How Much Does IFRS Cost? IFRS Adoption and Audit Fees - De George, Emmanuel T.; Ferguson, Colin B.; Spear, Nasser A. (The Accounting Review, 2013)
ABSTRACT This study provides evidence of a directly observable and significant cost of International Financial Reporting Standards (IFRS) adoption, by examining the fees incurred by firms for the statutory audit of their financial statements at the time of transition. Using a comprehensive dataset of all publicly traded Australian companies, we quantify an economy-wide increase in the mean level of audit costs of 23 percent in the year of IFRS transition. We estimate an abnormal IFRS-related increase in audit costs in excess of 8 percent, beyond the normal yearly fee increases in the pre-IFRS period. Further analysis provides evidence that small firms incur disproportionately higher IFRS-related audit fees. We then survey auditors to construct a firm-specific measure of IFRS audit complexity. Empirical findings suggest that firms with greater exposure to audit complexity exhibit greater increases in compliance costs for the transition to IFRS. Given the renewed debate about whether the Securities and Exchange Commission (SEC) should mandate IFRS for U.S. firms, our results are of timely importance. Data Availability: Data are publicly available from the sources identified in the paper. Survey response data are available from the authors upon request.